Analisis Putusan Pengadilan Tata Usaha Negara No. 118/g/2023/PTUN.MDN terhadap Sertifikat Hak Guna Usaha Perspektif Siyasah Qadaâ€™iyyah - Rambe, Noni; Khalid, Khalid (Legal Standing : Jurnal Ilmu Hukum, 2025)
Land disputes are complex legal issues that often trigger conflicts in Indonesia. Unclear administrative procedures, lack of legal certainty, and potential violations in the issuance of land certificates by the National Land Agency (NLA) often prolong disputes. This raises questions about the extent to which the judicial system can provide legal certainty and justice to the parties involved in the dispute. This study aims to examine the decision of the Medan PTUN Number 118/G/2023/PTUN.MDN regarding the dispute over the issuance of the Land Use Rights Certificate (LUR) between Abdullah Hasibuan and PT. Nubika Jaya. This study analyzes the judge's considerations in making the decision and reviews its compliance with the principles of fiqh siyasah, especially siyasah qada'iyyah. This study uses normative legal research methods with a statutory, analytical, and case approach. The results of the study indicate that the court considered that the certificate issued by the National Land Agency (NLA) was in accordance with applicable legal procedures, and no administrative legal defects were found.Â  This decision shows that in resolving land disputes, the principle of legal certainty and protection of legitimate rights holders is the main priority. Meanwhile, from the perspective of fiqh siyasah, especially siyasah qada'iyyah, this decision is consistent with the principles of justice ('adl) and legal certainty (istiqrar al-hukm). Although there are differences in the interpretation of the principles of good governance, justice in Islamic courts must consider the interests of all parties involved, including those who feel disadvantaged by administrative decisions.